Transparent Displays: Skin‐Like Oxide Thin‐Film Transistors for Transparent Displays (Adv. Funct. Mater. 34/2016). (12th September 2016) - Lee, Han Eol; Kim, Seungjun; Ko, Jongbeom; Yeom, Hye‐In; Byun, Chun‐Won; Lee, Seung Hyun; Joe, Daniel J.; Im, Tae‐Hong; Park, Sang‐Hee Ko; Lee, Keon Jae
Abstract : On page 6170, S.‐H. K. Park, K. J. Lee, and co‐workers demonstrate the construction of high‐performance, flexible, and transparent oxide thin‐film transistors (TFTs) by using an inorganic‐based laser lift‐off process. The 50 × 50 indium zinc oxide TFT arrays, fabricated on glass substrates, are transferred to ultrathin plastic substrates without structural damage. This method has great potential for realizing next‐generation flexible transparent displays.